Al-Tememe transformation for solving some types of PDEs with using initial and boundary conditions - Mohammed, Ali (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
The aim of this paper is to use the Al-Tememe transformation for solving some PDEs which have the general form At2utt + Btut + Ch1(x)uxx + Eh2(x)ux + Gh3(x)tutx + Pu = f (x; t) Where A,B,C,E,G and P are constants and f(x; t) is a function of x and t.